A motivational process model explaining L2 Saudi students' achievement of English. (December 2019) - Alamer, Abdullah; Lee, Jihyun
Abstract: The aim of the present study was to develop a motivational process model illustrating how Saudi students' Basic Psychological Needs (BPN) were linked to their second language (L2) achievement in English. Motivational theories that have been extensively researched in Educational Psychology were employed as possible mediators of the BPN-L2 achievement relationship. Those theories were: Self-determination Theory (SDT), Goal Orientation (GO) and Motivational Emotion (ME). The final model suggested that the temporal order of the mediational mechanism in explaining L2 achievement should be [BPN → GO → ME → SDT], indicating that (a) students' motivation starts with fulfillment of basic psychological needs, which (b) sets the foundation for students' goal setting orientation, which in turn (c) contributes to learners' emotions in learning. Further, this study support (d) the importance of the theoretical stream of Self-determination Theory, as it was the most directly related to L2 achievement.